Worldwide Census Data Reveal Prevalence of Educational Homogamy and Its Effect on Childlessness - Huber, Susanne; Fieder, Martin (Frontiers in Sociology, 2016)
In a former study based on US census data, we found that educational homogamy is common and reduces the odds to remain childless. This study takes the next step and examines the prevalence of educational homogamy and its association with childlessness as well as the number of children on a worldwide basis. We analyzed census data from 41 different countries encompassing a total of 2,179,736 married women. In all investigated countries, the prevalence of educational homogamy is high. Furthermore, educational homogamy is not associated with a woman’s average number of children, which generally increases with decreasing education. This is not the case as regards childlessness, however, which is usually reduced by a combination of moderate female hypergamy and homogamy. We conclude that educational homogamy is a universal phenomenon. We discuss that, together with its effects on childlessness, this may have consequences going beyond the individual to include the level of society and population genetics.